The impact of blood flow restriction training on tendon adaptation and tendon rehabilitation – a scoping review - Samuel Öberg; Ludvig von Schewelov; Eva Tengman (BMC Musculoskeletal Disorders)
Abstract Background Tendon injuries are common in athletes and in the general population and require extensive rehabilitation. Current conservative treatment often includes different high-load resistance training (HLRT) modalities. However, certain populations may not tolerate HLRT well. Blood flow restriction training (BFRT) incorporates low load while achieving hypertrophy and strength adaptations comparable to HLRT. However, the effects of BFRT on healthy and pathological tendons are unknown. The aims of this scoping review were therefore to summarize the reported impact of BRFT: (1) on tendon adaptation in healthy individuals, and (2) in tendon rehabilitation after injury. Methods A scoping review based on PRISMA guidelines was performed. A systematic literature search in the electronic databases PubMed, SPORTDiscus and CINAHL was performed in May 2024. This review includes peer-reviewed articles investigating the effects of BFRT on healthy tendons and in tendon rehabilitation. Methodological quality was assessed using the Downs and Black scale and JBI Critical Appraisal Checklist. Results 19 studies with varied design, population, investigated tendon, intervention design and outcome measures were eligible. Ten studies were randomized controlled trials (RCT), one study was a clinical controlled trial, three studies were feasibility studies and five were case reports. The reviewed studies included 351 healthy subjects and 122 individuals with tendon-related disorders (101 subjects with tendinopathy and 21 subjects with tendon ruptures). Tendons investigated were Achilles (n = 6), patellar (n = 6), hamstring (n = 1), gluteal (n = 1), biceps brachii distal (n = 1), tendons of the rotator cuff (n = 2) and lateral elbow extensors (n = 2). In the nine studies on healthy individuals, the effects of BFRT showed contradictory results regarding tendon-related outcomes. However, changes in outcome measures did not differ significantly from HLRT conditions or low-load resistance training (LLRT) conditions. The studies on tendon rehabilitation also showed contradictory results regarding tendon-related outcomes, although several studies do report decreased pain, increased strength, enhanced performance and improved self-reported diagnosis-specific function. Conclusions The present scoping review shows contradictory results regarding tendon-related outcomes although studies point to increasing tendon function after rehabilitation. BFRT may be a viable option to incorporate into training regimes aimed at inducing tendon adaptation. Further in-depth research is warranted. Clinical trial number This is a review and therefore is Clinical trial number: Not applicable. However, the review has been preregistered at www.osf.io (DOI https://doi.org/10.17605/OSF.IO/PYV43 ) stated in the method section.